Comparative evaluation of anti-bacterial efficacy of silver nanoparticle, nanoparticle calcium hydroxide and calcium hydroxide against enterococcus faecalis biofilm- An In vitro study - V., Dr.Abirami; Ahamed, Dr.A.Shafie; S., Dr.Bhavani; G., Dr.Rajaraman (International Journal of Dental Research, 2018)
The purpose of this study was to evaluate the antibacterial efficacy of silver Nanoparticles, Nanoparticle calcium hydroxide and calcium hydroxide as intracanal medicament against Enterococcus faecalis bio film formed on root dentinThe Minimal inhibitory concentration test and Anti microbial test were conducted for silver nanoparticle, Nanoparticle calcium hydroxide. Teeth were inoculated with E.faecalis strains for 1month to establish a standard mono species bio film model. Biofilm formation is confirmed using SEM. The intracanal medicaments were placed inside the canal and colony forming units (CFU) were counted before and 7 days later the placement of the medicament.MIC for AGNP is 25µg/200µl and for NCH is 12.5µg/200µl. The Antimicrobial test conducted shows zone of inhibition about 11mm and 14mm for AGNP and NCH respectively at 500µg. The calcium hydroxides do not show any antibacterial activity at this concentration. In antibacterial efficacy test using CFU count, the AGNP and NCH shows 75% and 61% of antibacterial efficacy respectively whereas calcium hydroxide has exhibited just 11% of antibacterial efficacy. Silver Nanoparticles and nanoparticle calcium hydroxide had statistically significant difference in the reduction in the number of colonies when compared to calcium hydroxide by post hoc turkey test and p-value of <0.01 was considered as significant in this study.